The Role of TEE in Diagnosing Hepatopulmonary Syndrome and Cryptogenic Cirrhosis. (31st August 2016) - Scott-Herridge, Joel; Bhagirath, Kapil; Janda, Surinder; Jassal, Davinder S.
Abstract : In the vast majority of cases, ongoing hypoxemia in a cirrhotic patient is usually hepatopulmonary syndrome (HPS) until proven otherwise; in this case, HPS was suspected prior to any known diagnosis of cirrhosis. This is the first reported case in the literature whereby HPS and cirrhosis were diagnosed after the fact, rather than with the preexisting knowledge of liver cirrhosis.